Enhanced self-regulation nonlinear PID for industrial pneumatic actuator - S. N S. Salim; M. F. Rahmat; L. Abdullah; S. A. Shamsudin; M. Zainon; A. F. M. Amin (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The present article describes the improvement of Self-regulation Nonlinear PID (SN-PID) controller. A new function is introduced to improve the system performance in terms of transient without affecting the steady state performance. It is used to optimize the nonlinear function available on this controller.  The signal error is reprocessed through this function, and the result is used to tune the nonlinear function of the controller. Furthermore, the presence of the dead zone on the proportional valve is solved using Dead Zone Compensator (DZC). Simulations and experiments were carried out on the pneumatic positioning system. Comparisons between the existing methods were examined and successfully demonstrated.